Bioelectrical impedance analysis-derived phase angle as a pragmatic screening tool for assessing sarcopenia in multi-ethnic peritoneal dialysis patients - Lee, Shi-Wah; Mat Daud, Zulfitri Azuan; Lim, Jun-Hao; Lim, Cordelia-Kheng-May; Ibrahim, Imliya; Chan, Yoke-Mun; Zakaria, Nor Fadhlina (Elsevier, 2024)
Objective: Sarcopenia, characterized by the loss of muscle mass and function, is prevalent in peritoneal dialysis (PD) patients. Early diagnosis is crucial, but universal screening is often hindered by the complexity of diagnostic algorithms and limited clinical resources. Therefore, this study aims to investigate the ability of bioelectrical impedance analysis-derived phase angle (PhA), a convenient and cost-effective technique, in detecting sarcopenia among PD patients. Methods: A single-center cross-sectional study was conducted on 130 multi-ethnic PD patients in Malaysia. Sarcopenia was assessed using Asian Working Group for Sarcopenia (AWGS) 2019 diagnostic algorithm. PhA was measured by a multi-frequency bioelectrical impedance analysis device at 50kHz. Multivariable logistic regression was used to determine predictability of PhA on sarcopenia. Receiver operating characteristics analysis was used to evaluate the discriminative performance of PhA in detecting sarcopenia. Optimal gender-specific PhA cut-off values for sarcopenia detection were determined based on desired sensitivity and specificity. Results: Sarcopenia was identified in 25.4% of the PD patients. PhA emerged as an independent predictor of sarcopenia (adjOR= 0.147; 95%CI =0.042–0.516; P =0.003), exhibiting excellent discriminative power in identifying sarcopenia (adjAUCoverall= 0.818±0.041; bootstrapped 95%CI =0.734–0.899, P <0.001). The optimal PhA cut-off values for sarcopenia detection were ≤4.05° (92.9% sensitivity and 53.8% specificity) and ≤3.75° (78.9% sensitivity and 51.1% specificity) for male and female patients, respectively. Conclusion: PhA serves as a pragmatic screening tool for identifying multi-ethnic Malaysian PD patients at risk of sarcopenia, facilitating early diagnosis and intervention to improve patient outcomes.